2008
DOI: 10.1080/00365510701883172
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic antigen, neuron‐specific enolase and cytokeratin fragment 19 (CYFRA 21‐1) levels in induced sputum of lung cancer patients

Abstract: Of tumour markers in induced sputum, sputum CYFRA 21-1 offered the best predictive values, although not sufficiently satisfactory to suggest its routine use in lung cancer diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Serum CYFRA 21-1 level was not influenced by sex and smoking habits [38, 39], which was found to be an independent prognostic factor of survival and tumour relapse [40]. The meta-analysis about prognostic significance of CYFRA 21-1 has been studied in several articles, which have indicated that high level expression of CYFRA 21-1 implies a poor prognosis [32, 34, 4148]. In this study, we found that the 2-year overall survival in the high level group was significantly lower than that in the low level group group, which is consistant with studies previous.…”
Section: Discussionmentioning
confidence: 99%
“…Serum CYFRA 21-1 level was not influenced by sex and smoking habits [38, 39], which was found to be an independent prognostic factor of survival and tumour relapse [40]. The meta-analysis about prognostic significance of CYFRA 21-1 has been studied in several articles, which have indicated that high level expression of CYFRA 21-1 implies a poor prognosis [32, 34, 4148]. In this study, we found that the 2-year overall survival in the high level group was significantly lower than that in the low level group group, which is consistant with studies previous.…”
Section: Discussionmentioning
confidence: 99%
“…27 Elevated CYFRA 21-1 levels have also been shown in induced sputum of lung cancer patients. 28 The current study of CYFRA 21-1 did not have controls of other malignancies.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, serum tumour markers are not useful in lung cancer diagnosis (1). The diagnosis of lung cancer is based on the histological and cytological examination of material usually obtained by bronchoscopy (endobronchial biopsies, washings, and brushings) (19). However, despite the high sensitivity of this technique in detecting tumours, in some cases false negative results can be seen (20).…”
Section: Introductionmentioning
confidence: 99%
“…The source of bronchogenic carcinoma is the bronchial epithelium (19). In addition, ADA production by neoplastic cells is increased (4,7) and it could be assumed that respiratory secretions from lung cancer patients may contain high levels of ADA.…”
Section: Introductionmentioning
confidence: 99%